Development and validation of the educational leadership scale for mental health providers: A network analysis approach - Wafa Mohammed Aldighrir (Humanities & Social Sciences Communications)
Abstract Educational leadership skills are essential for mental health providers to provide high-quality, patient-centered mental health services and promote mental well-being in the community. The current study developed and examined the Psychometric Properties of the Educational Leadership Scale for Mental Health Providers (ELSM). Literature review, Delphi method, and item composition methods were used to develop ELSM. The final version of ELSM included 23 items rated on a Likert scale ranging from 1 (strongly Disagree) to 5 (Strongly Agree). Both Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were employed to assess the scale’s construct validity with different subsamples allocated randomly. Reliability indices, including Cronbach’s alpha, McDonald’s omega, and test-retest reliability, were also calculated. Furthermore, the study utilized a network perspective, incorporating Exploratory Graph Analysis (EGA) and centrality measures (betweenness, closeness, and strength). Five hundred eighty-five mental health providers (mean age: 37.5 ± 9.77 years; 58.1% female) participated in the current study. Both EFA and CFA indicated that the ELSM, consisting of 23 items and six dimensions, was the optimal solution. The ELSM demonstrated good reliability (Cronbach’s alpha coefficient was 0.809). Six distinct factors emerged: Instructional leadership (α = 0.801), collaborative leadership (α = 0.806), scientific leadership (α = 0.791), ethical leadership (α = 0.781), visionary leadership (α = 0.755), and transformational leadership (α = 0.781). Centrality measures revealed that item.3 (associated with Instructional leadership), item 7 (associated with Scientific Leadership), and item.23 (associated with Collaborative leadership) emerged as the most central nodes. Lastly, the McDonald’s omega coefficient for the total scale was estimated to be 0.84. The ELSM demonstrates strong validity and reliability with six distinct leadership dimensions. It is a valuable tool for assessing leadership skills in mental health providers.